2013
DOI: 10.4014/jmb.1307.07051
|View full text |Cite
|
Sign up to set email alerts
|

Biominerlization and Possible Endosulfan Degradation Pathway Adapted by Aspergillus niger

Abstract: Endosulfan is a chlorinated pesticide; its persistence in the environment and toxic effects on biota are demanding its removal. This study aims at improving the tolerance of the previously isolated fungus Aspergillus niger (A. niger) ARIFCC 1053 to endosulfan. Released chloride, dehalogenase activity, and released proteins were estimated along with analysis of endosulfan degradation and pathway identification. The culture could tolerate 1,000 mg/ml of technical grade endosulfan. Complete disappearance of endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Studies show that the half-life of endosulfan sulfate is approximately 120 days, (Bhalerao, 2013), so the presence of this compound in the samples analyzed shows the constant use of this molecule in agricultural areas near the Inner Bay of Lake Titicaca.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies show that the half-life of endosulfan sulfate is approximately 120 days, (Bhalerao, 2013), so the presence of this compound in the samples analyzed shows the constant use of this molecule in agricultural areas near the Inner Bay of Lake Titicaca.…”
Section: Resultsmentioning
confidence: 98%
“…All sediment samples analysis show the contamination by endosulfan sulfate in concentrations from 0.0004 to 0.006 μg/g, a stable metabolite of endosulfan (Snedeker & Hay, 2012;Bhalerao, 2013), nevertheless, its use was prohibited in Peru since 2012 by the national agricultural health service SENASA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A rapid complete mineralization of 1.0 g•L −1 endosulfan within a week by the A. niger ARIFCC 1053 strain was reported by Tejomyee [33]. It was suggested that the degradation was initiated by the oxidation to endosulfan sulfate and its hydrolysis to endosulfan diol.…”
Section: Degradation Of Organochlorine Pesticides By Aspergillus and ...mentioning
confidence: 84%